The most common and predicted diagnosis or conditions of oral mucosal lesions among elementary school children - Wahyuni, Indah Suasani; Putri, Fidya Meditia; Fatriadi, Fajar; Nur'aeny, Nanan; Hidayat, Wahyu (Padjadjaran Journal of Dentistry, 2021)
Introduction: Oral mucosal health is part of general health that also requires attention. Research on oral mucosal in children has not widely conducted, especially in the Jatinangor sub-district as one of the educational centres in West Java.  This study was aimed to determine the most common and predicted the diagnosis or conditions of oral mucosal lesions among elementary school children. Methods: This research was a cross-sectional study. The purposive sampling method was used, in which only the fifth-grade students from the elementary school cluster near the centre of the Jatinangor sub-district were involved. The inclusion criteria were healthy condition, cooperative, able to communicate with the examiner, and obtained permission from the parent/guardian. The oral mucosal lesions were examined using disposable dental tools and a white light headlamp. Oral mucosal lesions found on examination defined as oral diseases and normal variation of oral mucosal. Results: A total of 226 students, consisting of 115 males and 111 females, were included in this study. The oral mucosal lesions found were described as follows: 100 cases of pseudomembranous plaque, 106 cases of macula, 56 cases of ulceration, 45 cases of cheek biting, and another fewer lesions. The lesions' diagnosis was coated tongue for the pseudomembranous plaque, physiologic pigmentation for the macula, aphthous stomatitis/traumatic ulcer/angular cheilitis for ulcers, linea alba for cheek biting, and others. Conclusion: The most commonly found oral mucosal lesions were macula which is diagnosed as macular hyperpigmentation, followed by pseudomembranous plaque which is diagnosed as coated tongue.